Genetic diversity and structure of astrocaryum jauari (mart.) palm in two amazon river basins - Oliveira, Liliane D Santos; Ramos, Santiago Linorio Ferreyra; Lopes, Maria Teresa Gomes; Dequigiovanni, Gabriel; Veasey, Elizabeth Ann; Macedo, Jeferson Luis Vasconcelos de; Batista, Jacqueline da Silva; Formiga, Kyara M.; Lopes, Ricardo (Crop Breeding and Applied Biotechnology, 2014)
Astrocaryum jauari is a non-domesticated palm that is exploited by poachers. Our objective was to investigate the organization of the genetic diversity and structure of three A. jauari populations. The study was carried out in the state of Amazonas, between the municipalities of Coari and Manaus. Nine microsatellite loci were used for the genetic analyses. High genetic variation was found, with a mean number of alleles per locus varying from 3.9 to 4.4. The average observed heterozygosity, varying from 0.71 to 0.78, was higher than expected. No spatial genetic structure was detected, since only one cluster was observed. Our results indicate a possible dispersion strategy and suggest that conservation measures of this species should focus mainly on the populations found at the end of the main river (Solimões) where most of the plant material originating from the headwaters of the tributaries of this river is concentrated. © 2014 Brazilian Society of Plant Breeding. All rights reserved.
Marcadores microssatélites revelam a diversidade genética e estrutura da palmeira astrocaryum jauari (mart.)